LED electric-measuring indicators for multithreshold comparators - Oborskii, G. A.; Koval’kov, V. I.; Tikhenko, V. N.; Slobodyanik, P. T. (Technology and design in electronic equipment, 2012)
Сonstruction principles of electric-measuring indicators with optical scales, controlled directly by multithrashold voltage or current comparators are considered. The introduced measuring devices with LED indicators with improved resolution may become an alternative to the series-produced foreign devices.